2018
DOI: 10.3389/fphar.2017.00973
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Value of ALCAM as a Target Gene of microRNA-483-5p in Patients with Early Recurrence in Hepatocellular Carcinoma

Abstract: The long-term survival rate of hepatocellular carcinoma (HCC) is poor. One of the reasons for the poor rate of survival is the high rate of recurrence caused by intrahepatic metastas is that adversely affects long-term outcome. Many studies have indicated that microRNAs play an important role in HCC, but there has been no research of clonal origins on recurrent HCC (RHCC) by analzing microRNAs. In the present study, we found that miR-483-5p was significantly upregulated in RHCC tissues of short-term recurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…ALCAM expression can also be regulated by microRNAs. For example, microRNA-192, miR-148b-3p, miR-152, and miR-483-5p have been shown to be able to suppress the expression of ALCAM in tumour cells, including gastric, pituitary, and liver cancer cells, possibly by targeting the 3 -UTR binding site of the transcription region of ALCAM gene [19][20][21][22].…”
Section: Alcam Expression and Its Functional Influence In Cancer Cellsmentioning
confidence: 99%
“…ALCAM expression can also be regulated by microRNAs. For example, microRNA-192, miR-148b-3p, miR-152, and miR-483-5p have been shown to be able to suppress the expression of ALCAM in tumour cells, including gastric, pituitary, and liver cancer cells, possibly by targeting the 3 -UTR binding site of the transcription region of ALCAM gene [19][20][21][22].…”
Section: Alcam Expression and Its Functional Influence In Cancer Cellsmentioning
confidence: 99%
“…MiR-126 and miR-1185 regulate endothelial expression of VCAM1 [63,108]. ALCAM is reported as a target gene of miR-483-5p [64].…”
Section: Extravasationmentioning
confidence: 99%
“…Growing evidence indicates that the deregulation of miRNAs occurs in HCC progression 29 and recent studies have further developed the miRNA-based risk of HCC recurrence following liver resection. 30 Results of miRNA therapies in HCC showed that either reintroducing suppressor miRNAs or inhibiting oncogenic miRNAs suppress HCC progression in various HCC cell lines in vitro, animal models in vivo, and human clinical trials. 31 Our work provides additional details, identifying a specific miRNA and its target gene, which are involved in the regulation of HCC proliferation.…”
Section: Discussionmentioning
confidence: 99%